Pembuatan Kue Pukis dengan Proporsi Pure Ubi Jalar Ungu (Ipomoea batatas L.) dan Pure Talas (Colocasia esculenta) - Nensi Pratiwi; Niken Purwidiani; Mauren Gita Miranti; Any Sutiadiningsih (Pusat Riset dan Inovasi Nasional, 2023)
Pukis cake is a typical Indonesian wet cake with the basic ingredients of wheat flour. The low consumption of local food ingredients by the community, it is necessary to make pukis cakes by utilizing local food ingredients. Wheat can be replaced with local foodstuffs that have a high starch such as purple sweet potato and taro potato. This problem is the aim of this study to determine the sensory quality of purple sweet potato puree pukis cake and taro sweet potato puree which includes color, shape, aroma, texture, taste. Knowing the nutritional and non-nutritional content which includes antioxidants, protein, fat, carbohydrates, ash, and vitamin C, laboratory tests are carried out, and material costs are calculated. Data collection uses the observation method through sensory tests. The result data were processed with the Anova test followed by the Duncan test. The results showed: 1)The sensory quality of purple sweet potato puree pukis and taro sweet potato puree produced products categorized as good (40%:20%). 2)The nutritional and non-nutritional contents of the product are Antioxidants 8.16%, Protein 6.15%, Fat 3.10%, Carbohydrates 56.01%, Ash 1.39% and Vitamin C 16.88 mg. 3) The material cost of purple sweet potato puree pukis cake and taro pure potato cake is known to be IDR 30,920. Research conclusions 1)The product is expressed well in color, aroma, texture, taste. 2)The use of local food ingredients has an effect on adding product nutrition. 3)The cost of making the product is IDR 30,920.